2018
DOI: 10.3126/jnps.v37i2.18307
|View full text |Cite
|
Sign up to set email alerts
|

Role of Micro- and Mesosystems in Shaping an Adolescent

Abstract: Adolescence is a vulnerable period in an individual's life during which several physiological and psychological changes occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Originating within developmental psychology and sociology, this model views young people’s development as being influenced by their relationships with close family members, school, friends, their community and the wider socio-politico-cultural context. A recent example of this would be Chandrasekaran et al (2017) review who, using Bronfenbrenner’ model as a framework, explored the impact of the micro- and meso-systems upon delinquent behaviour in adolescents. It is suggested that this can be further extended to study identity development pre- and post-rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Originating within developmental psychology and sociology, this model views young people’s development as being influenced by their relationships with close family members, school, friends, their community and the wider socio-politico-cultural context. A recent example of this would be Chandrasekaran et al (2017) review who, using Bronfenbrenner’ model as a framework, explored the impact of the micro- and meso-systems upon delinquent behaviour in adolescents. It is suggested that this can be further extended to study identity development pre- and post-rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…The reason is that most of the teachers are providing low-cost materials from the budget they received from the school and at their own expense to fill the gap. According to Bronfenbrenner's Ecological System Theory, space, place and available resources are the immediate settings around young children [99], and they create the learning environment [100]. However, the qualitative data showed that enough resources were not provided, due to lack of budget.…”
Section: Discussionmentioning
confidence: 99%